125 Safety and Efficacy of the Pipeline Embolization Device in 100 Small Intracranial Aneurysms. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Chalouhi, Nohra; Zanaty, Mario; Whiting, Alex; Yang, Steven; Tjoumakaris, Stavropoula I.; Hasan, David M.; Starke, Robert M.; Hann, Shannon W.; Hammer, Christine; Kung, David; Rosenwasser, Robert H.; Jabbour, Pascal
Abstract: INTRODUCTION: In most series, the pipeline embolization device (PED) is used for the treatment of large, giant, complex, and fusiform aneurysms. Little is known about the use of the PED in small aneurysms. The purpose of this study was to assess the safety and efficacy of the PED in small aneurysms (=7 mm). METHODS: A total of 100 consecutive patients were treated with the PED at our institution between May 2011 and September 2013. Data on procedural safety and efficacy was retrospectively collected. RESULTS: Mean aneurysm size was 5.2 ± 1.5 mm. Seven patients had sustained a subarachnoid hemorrhage. The number of PEDs used was 1.2/aneurysm. Symptomatic procedure-related complications (3%) were: 1 distal parenchymal hemorrhage and 2 ischemic events. At the latest follow-up (mean, 6.1 months), 52 (71%) aneurysms were completely occluded (100%), 10 (14%) were near-completely occluded (=90%), and 11 (15%) were incompletely occluded (<90%). Six aneurysms (8%) required further treatment. Increasing aneurysm size (OR = 3.9; 95% CI, 0.99-15; P = .05) predicted retreatment. All patients achieved a favorable outcome (mRS 0-2) at follow-up. CONCLUSION: Treatment of small aneurysms with the PED was associated with low complication rates and high aneurysm occlusion rates. This suggests that the PED is a safe and effective alternative to conventional endovascular techniques for small aneurysms. Randomized trials with long-term follow-up are necessary to determine the optimal type of treatment.